Autonomous Surface Vessel with Remote Human on the Loop: System Design for STCW Compliance. Issue 16 (2021) - Dittmann, Kjeld; Hansen, Peter Nicholas; Papageorgiou, Dimitrios; Jensen, Signe; Lützen, Marie; Blanke, Mogens
Abstract: Autonomous surface vessels comprise complex automated systems with advanced onboard sensors. These help establish situation awareness and perform many of the complex tasks required for safe navigation. However, situations occur that require assistance by a human proxy. If not physically present on board, information digestion and sharing between human and machine become crucial to maintain safe operation. This paper addresses the co-design of on-board systems and a Remote Control Centre (RCC). Using the international regulations on watch-keeping (STCW) as a basis, the paper discuss how an autonomous system is designed to meet the STCW requirements. It is discussed how the autonomous system is made aware of the state of the vessel, its surroundings, on-board defects or navigational challenges and shared with the RCC in a collaborating system perspective.